Detection of Na, K, and H2O in the hazy atmosphere of WASP-6b. Issue 4 (22nd April 2020) - Carter, Aarynn L; Nikolov, Nikolay; Sing, David K; Alam, Munazza K; Goyal, Jayesh M; Mikal-Evans, Thomas; Wakeford, Hannah R; Henry, Gregory W; Morrell, Sam; López-Morales, Mercedes; Smalley, Barry; Lavvas, Panayotis; et al.
ABSTRACT: We present new observations of the transmission spectrum of the hot Jupiter WASP-6b both from the ground with the Very Large Telescope FOcal Reducer and Spectrograph (FORS2) from 0.45 to 0.83 μm, and space with the Transiting Exoplanet Survey Satellite from 0.6 to 1.0 μm and the Hubble Space Telescope ( HST ) Wide Field Camera 3 from 1.12 to 1.65 μm. Archival data from the HST Space Telescope Imaging Spectrograph (STIS) and Spitzer are also re-analysed on a common Gaussian process framework, of which the STIS data show a good overall agreement with the overlapping FORS2 data. We also explore the effects of stellar heterogeneity on our observations and its resulting implications towards determining the atmospheric characteristics of WASP-6b. Independent of our assumptions for the level of stellar heterogeneity we detect Na i, K i, and H2 O absorption features and constrain the elemental oxygen abundance to a value of [O/H] ≃ −0.9 ± 0.3 relative to solar. In contrast, we find that the stellar heterogeneity correction can have significant effects on the retrieved distributions of the [Na/H] and [K/H] abundances, primarily through its degeneracy with the sloping optical opacity of scattering haze species within the atmosphere. Our results also show that despite this presence of haze, WASP-6b remains a favourable object for future atmospheric characterization with upcoming missions such as the James Webb Space Telescope .